Fruits of the future: the results of the project ‘Fruits in line with science’ - N. G. Tikhonova; Yu. V. Ukhatova; A. A. Zavarzin; D. R. Vladimirov; A. A. Iurmanov (Труды по прикладной ботанике, генетике и селекции)
The paper covers the results of the civic science project that involved VIR partners – Russian Geographical Society, Russian Schoolchildren’s Movement and the Association of Communicators in Education and Science – as organizers and schoolchildren, students and their parents from different regions of Russia as participants. The project, started in 2020 with observations of a single crop – an apple tree, elicited a positive response from motivated schoolchildren and was continued in 2021–2022 with the inclusion of various fruit and berry crops. In the course of the three years of the project, a phenological database was replenished with 3340 entries made by 670 project participants.